A new angle for probing field‐aligned irregularities with the Murchison Widefield Array. Issue 6 (14th June 2016) - Loi, Shyeh Tjing; Murphy, Tara; Cairns, Iver H.; Trott, Cathryn M.; Hurley‐Walker, Natasha; Feng, Lu; Hancock, Paul J.; Kaplan, David L.
Abstract: Electron density irregularities in the ionosphere are known to be magnetically anisotropic, preferentially elongated along the lines of force. While many studies of their morphology have been undertaken by topside sounding and whistler measurements, it is only recently that detailed regional‐scale reconstructions have become possible, enabled by the advent of widefield radio telescopes. Here we present a new approach for visualizing and studying field‐aligned irregularities (FAIs), which involves transforming interferometric measurements of total electron content gradients onto a magnetic shell tangent plane. This removes the perspective distortion associated with the oblique viewing angle of the irregularities from the ground, facilitating the decomposition of dynamics along and across magnetic field lines. We apply this transformation to the data set of Loi et al. (2015a), obtained on 15 October 2013 by the Murchison Widefield Array (MWA) radio telescope and displaying prominent FAIs. We study these FAIs in the new reference frame, quantifying field‐aligned and field‐transverse behavior, examining time and altitude dependencies, and extending the analysis to FAIs on subarray scales. We show that the inclination of the plane can be derived solely from the data and verify that the best fit value is consistent with the known magnetic inclination. The ability of the model to concentrate the fluctuations along a single spatial direction may find practical application to future calibration strategies for widefield interferometry, by providing a compact representation of FAI‐induced distortions. Key Points: Introduce new transformation scheme mapping interferometric TEC gradient data onto magnetic shell tangent plane Physically meaningful coordinates enable decomposition of field‐transverse and field‐aligned behavior Demonstrate technique for measuring magnetic inclination from TEC data and verify geomagnetic alignment of irregularities observed by MWA